2001
DOI: 10.1063/1.1367407
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics of dislocations in highly boron-doped silicon

Abstract: The dynamic behavior of dislocations in highly boron (B)-doped Si crystals with concentration up to 2.5×1020 cm−3 is investigated using the etch pit technique. Suppression of the generation of dislocations from a surface scratch is found for B-doped Si and the critical stress for dislocation generation increases with B concentration, which is interpreted in terms of dislocation locking due to impurity segregation. The velocity of dislocations in B-doped crystals is revealed to increase by increasing the B conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…In fact, dislocation peaks such as D3 and D4 lines may still be present, but might be masked by the PL signal of continuous deep levels formed by the laser doping process [11]. It is additionally possible that the density of intrinsic dislocations (D3 and D4) might actually be suppressed due to the dislocation pinning effect of boron dopants in the laser-doped region, as reported previously for heavily doped silicon [32,33].…”
Section: Pl Spectra Of Excimer Laser Boron-doped Silicon Substratesmentioning
confidence: 88%
“…In fact, dislocation peaks such as D3 and D4 lines may still be present, but might be masked by the PL signal of continuous deep levels formed by the laser doping process [11]. It is additionally possible that the density of intrinsic dislocations (D3 and D4) might actually be suppressed due to the dislocation pinning effect of boron dopants in the laser-doped region, as reported previously for heavily doped silicon [32,33].…”
Section: Pl Spectra Of Excimer Laser Boron-doped Silicon Substratesmentioning
confidence: 88%
“…At present, CZ-Si crystals containing oxygen atoms at a concentration of ~10 18 cm -3 are used exclusively in industry on account of their high critical resolved shear stress for dislocation generation [12] and high mechanical strength in comparison with float-zone Si crystals [13]. Basically, oxygen impurities interstitially dissolved in Si crystals have been found to preferentially segregate on and immobilize dislocations, leading to high mechanical stability of the crystal [14].…”
Section: Introductionmentioning
confidence: 99%
“…Imai and Sumino measured the dislocation velocity in boron doped silicon and reported the boron doping slightly decreases the dislocation velocity. 17) Yonenaga et al 20) reported that a certain level of stress is necessary to make dislocations start gliding in Czochralski (CZ) silicon and that the dislocation velocity is slightly increased by heavily boron doping at the high stress level. Erofeev et al 21) reported the effect of boron on dislocation velocity changes contrary below or above of a critical temperature.…”
Section: Introductionmentioning
confidence: 99%